Australia : 2012 Article IV Consultation-Staff Report; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Australia. (IMF Staff Country Reports; Country Report ;, 2012)
GDP growth is likely to remain strong, although narrowly driven by a mining investment boom, increasing the economy's vulnerability to terms of trade shocks. Outside the mining sector, growth is expected to be slow with still weak consumer confidence and a strong exchange rate weighing on business investment. The main risks are external, and include an intensification of the euro crisis and a sharper-than-expected slowdown in China.